2021
DOI: 10.1016/j.jhin.2020.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the infection prevention and control core components at the national level: a global situational analysis

Abstract: feedback of IPC indicators was reported by 65.9%. Only 12.5% of countries had all core components in place. Conclusion: Most countries have IPC programme and guidelines, but many less have invested adequate resources and translated them in implementation and monitoring, particularly in low-income countries. Leadership support at the national and global level is needed to achieve implementation of the core components in all countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 28 publications
3
68
0
5
Order By: Relevance
“…24 25 A WHO survey of 88 countries to assess implementation of the WHO core components of an IPC programme found that only 54% had in-service IPC training. 26 Over half (18 of 32) of national nursing associations reported IPC training had not been provided within 6 months of the pandemic's start. 27 Supportive supervision and mentorship for health facilities are also part of an effective IPC programme 2 and contribute to improved quality of care and strengthened health systems.…”
Section: Summary Boxmentioning
confidence: 99%
See 3 more Smart Citations
“…24 25 A WHO survey of 88 countries to assess implementation of the WHO core components of an IPC programme found that only 54% had in-service IPC training. 26 Over half (18 of 32) of national nursing associations reported IPC training had not been provided within 6 months of the pandemic's start. 27 Supportive supervision and mentorship for health facilities are also part of an effective IPC programme 2 and contribute to improved quality of care and strengthened health systems.…”
Section: Summary Boxmentioning
confidence: 99%
“…29 Second, programme monitoring and systematic use of data are needed to identify persistent gaps and to implement evidence-based policies; however, only 66% (58 of 88) of WHO-surveyed countries monitored IPC-related indicators, with a lower proportion among LMICs. 26 Third, limited resources and infrastructure in LMICs pose even greater challenges, [29][30][31][32] 33 which was later adapted and published by the Africa Centres for Disease Control and Prevention, 34 was developed in both English and French based on the IPC hierarchy-source controls, administrative controls, environmental controls and PPE 35 -for use by implementing partners at primary healthcare settings.…”
Section: Summary Boxmentioning
confidence: 99%
See 2 more Smart Citations
“…In a large multi-country study, national IPC focal points were interviewed to assess the level of implementation of IPC programmes at the national level [ 8 ]. Among the low-income countries interviewed, only nine (45%) reported the existence of a national IPC programme; four (20%) had documents on implementation strategies; one (5%) monitored compliance with IPC practices.…”
Section: Introductionmentioning
confidence: 99%